Anesthetic action on extra-synaptic receptors: effects in neural population models of EEG activity - Hashemi, Meysam; Hutt, Axel; Sleigh, Jamie (Frontiers in Systems Neuroscience, 2014)
The role of extra-synaptic receptors in the regulation of excitation and inhibition in the brain has attracted increasing attention. Because activity in the extra-synaptic receptors plays a role in regulating the level of excitation and inhibition in the brain, they may be important in determining the level of consciousness. This paper reviews briefly the literature on extra-synaptic GABA and NMDA receptors and their affinity to anesthetic drugs. We propose a neural population model that illustrates how the effect of the anesthetic drug propofol on GABAergic extra-synaptic receptors results in changes in neural population activity and the electroencephalogram (EEG). Our results show that increased tonic inhibition in inhibitory cortical neurons cause a dramatic increase in the power of both delta and alpha bands. Conversely, the effects of increased tonic inhibition in cortical excitatory neurons and thalamic relay neurons have the opposite effect and decrease the power in these bands. The increased delta activity is in accord with observed data for deepening propofol anesthesia; but is absolutely dependent on the inclusion of extra synaptic (tonic) GABA action in the model.